The effectiveness of SAPE: A technology-based interactive learning media for enhancing solfeggio ability of senior high school students - Ronald Elisa; Yohanes Bahari; Dede Suratman; Martono Martono; Muhammad Basri (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2026)
This study addresses the challenge of deficient solfeggio proficiency amongst Year 11 students at SMAN 01 Jagoi Babang, a limitation that invariably leads to suboptimal musical performance, particularly for individuals with diminished pitch perception. The primary objective was to rigorously evaluate the efficacy of the SAPE (Senang Aktif Piano Efektif / Happy Active Piano Effective) interactive media in enhancing solfeggio capabilities within the music curriculum. Employing a quantitative approach, the research utilised a quasi-experimental, non-equivalent control-group design within a two-cycle Classroom Action Research framework. This methodology facilitated the precise measurement of proficiency trajectories through comparative analysis. The participant cohort comprised 36 students identified with pitch-perception difficulties via a diagnostic assessment, who were subsequently allocated to homogeneous experimental and control groups through purposive sampling. Data were systematically gathered via a pretest-posttest practical examination targeting sight-reading, ear training, and sight-singing, along with a Likert-scale questionnaire to capture affective responses. The findings demonstrate that the experimental group, utilising the SAPE intervention, achieved consistently superior improvements in solfeggio proficiency compared to the control group subjected to conventional pedagogical methods. Furthermore, SAPE functions as a highly efficacious multimodal instructional tool, fostering active engagement, augmenting self-confidence, and enabling independent, offline practice. Ultimately, this study substantiates that innovative interactive media, particularly when integrating local wisdom, serve as a critical determinant in the successful delivery of secondary school music education.